2022
DOI: 10.1515/jcim-2021-0457
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic management of radiation-induced mucositis using herbal mouthwash in patients with head and neck cancer: an assessor-blinded randomized controlled trial

Abstract: Background and objectives Radiation-induced mucositis (RIOM) is one of the most common side effects from head and neck radiotherapy. Several reagents have been introduced to manage the symptom; however, there is still a limited number of effective reagents. Herbal mouthwashes with payayor (Clinacanthus nutans Lindau) and fingerroot (Boesenbergia rotunda) were tested their efficacies in preventing and reducing severity of RIOM in comparison with normal saline with sodium bicarbonate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…In contrast, payayor and fingerroot mouthwashes analyzed by Kongwattanakul et al [ 11 ], Cystus tea mouthwash used by Ebert et al [ 15 ], green tea mouthwash used by Liao et al [ 16 ], propolis mouthwash by Hamzah et al [ 18 ], and curcumin mouthwash studied by Shah et al [ 21 ] have been shown to be equally effective compared to placebo mouthwash, especially when assisted with cryotherapy and laser or light therapy [ 16 ]. The multicenter study by De Sanctis et al [ 17 ] also found no differences in the onset and severity of radio-induced mucositis with Lactobacillus brevis CD2 supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, payayor and fingerroot mouthwashes analyzed by Kongwattanakul et al [ 11 ], Cystus tea mouthwash used by Ebert et al [ 15 ], green tea mouthwash used by Liao et al [ 16 ], propolis mouthwash by Hamzah et al [ 18 ], and curcumin mouthwash studied by Shah et al [ 21 ] have been shown to be equally effective compared to placebo mouthwash, especially when assisted with cryotherapy and laser or light therapy [ 16 ]. The multicenter study by De Sanctis et al [ 17 ] also found no differences in the onset and severity of radio-induced mucositis with Lactobacillus brevis CD2 supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also compared the effectiveness of plant extract and natural substance-based mouthwashes with saline, baking soda-based, or placebo mouthwashes. The effectiveness of these mouthwashes is often comparable to bicarbonate-based saline solution rinses [64][65][66]. Granulocyte-macrophage colonystimulating factor mouthwashes are the most studied for the prevention of mucositis [67].…”
Section: Radiation-induced Mucositismentioning
confidence: 99%
“…Its incidence among patients receiving chemotherapy and radiotherapy reaches 80%.5 50% of the patients who receive radiotherapy treatment to the head and neck area experience 3rd stage mucositis (4)(5). Ulcers caused by damage to the oral mucosa pose a serious risk for bacterial contamination and systemic infection (6). It is very painful, makes speech difficult, affects chewing, swallowing, and oral intake of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…The correct management of oral mucositis means to take preventive approaches in a timely manner and to minimize the patient's distress by providing pain assessment and management (7). In addition to the granulocyte monocyte colony stimulating factor, topical corticosteroids used in mucositis management, honey is reported to be an effective approach to prevent oral mucositis (6,(8)(9)(10)(11)(12). Honey has been used since the Egyptian civilization, it is used in modern medicine for burn wounds, oral infections and surgical wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation